2010
DOI: 10.1111/j.1349-7006.2009.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cholangiocarcinoma: An update focusing on risk factors

Abstract: Cholangiocarcinoma is relatively rare, but high incidence rates have been reported in Eastern Asia, especially in Thailand. The etiology of this cancer of the bile ducts appears to be mostly due to specific infectious agents. In 2009, infections with the liver flukes, Clonorchis sinensis or Opistorchis viverrini, were both classified as carcinogenic to humans by the International Agency for Research on Cancer for cholangiocarcinoma. In addition, a possible association between chronic infection with hepatitis B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
300
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(307 citation statements)
references
References 65 publications
4
300
0
3
Order By: Relevance
“…Liver fluke caused by Opisthorchis viverrini, is a health problem in Thailand particularly in the northeast and north region (IARC, 1994;Shin et al, 2010;Sripa et al, 2010;Sithithaworn et al, 2012;Wongsaroj et al, 2014;Kaewpitoon et al, 2015e). O. viverrini infection is the etiology of cholangiocarcinoma (CCA) (Thamavit et al, 1978;Sripa et al, 2007;Sripa et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liver fluke caused by Opisthorchis viverrini, is a health problem in Thailand particularly in the northeast and north region (IARC, 1994;Shin et al, 2010;Sripa et al, 2010;Sithithaworn et al, 2012;Wongsaroj et al, 2014;Kaewpitoon et al, 2015e). O. viverrini infection is the etiology of cholangiocarcinoma (CCA) (Thamavit et al, 1978;Sripa et al, 2007;Sripa et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental and epidemiological evidences 1 strongly indicated that O. viverrini infection is the etiology of cholangiocarcinoma (CCA) (Thamavit et al, 1978;IARC, 1994;Sripa et al, 2007), and CCA has been reported that Thailand is the highest incident of the world (Green et al, 1991;Sripa, et al, 2007;Kaewpitoon et al, 2008a;Shin, et al, 2010). CCA was the caused of death in Thai population and found that CCA was ranked 4 in male and 5 in female (Sripa and Pairojkul, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The liver fluke, Opisthorchis viverrini (OV), continues to be a serious public health problem in north and northeast Thailand, associated with a very high incidence of cholangiocellular carcinoma (Shin et al, 2010). Over six million Thai people are estimated to be infected, and the highest prevalence rates are found in Issan and to a lesser extent in the North.…”
Section: Introductionmentioning
confidence: 99%